The Togo national proficiency test pilot programme for basic clinical chemistry tests - Kafui C. Kouassi; Améyo M. Dorkenoo; Komivi Gbada; Yaovi-Gameli Afanyibo; Minogblon Têko; Adjane Koura (AOSIS, 2022)
Background: A national proficiency test (PT) programme is not currently implemented in most low-income countries. However, participation in such PT programmes assists improves test performance and result accuracy. Objective: This study assessed how well 11 government hospital laboratories performed 18 basic clinical chemistry tests and identified areas needing improvement. Methods: A cross-sectional study was carried out by the Division of Laboratories of the Ministry of Health of Togo from 01 July 2016 to 31 December 2016. The test performance was evaluated using panels provided by One World Accuracy, Canada (Vancouver). The Clinical Laboratory Improvement Amendments criteria were used in evaluating the laboratories, and their success rates were compared with the World Health Organization Regional Office for Africa's target of 80%. Results: The overall rate of acceptable results at the laboratories was over 80% for glucose, alanine aminotransferase, aspartate aminotransferase, gamma-glutamyltransferase, alkaline phosphatase and triglycerides tests. The laboratories using fully automated spectrophotometers had an acceptable results rate of 89% (p = 0.001). The overall performance of the laboratories by cycles varied from 71% to 82%. Conclusion: This national PT programme identified the tests, which laboratories must improve their performance (urea, creatinine, uric acid, bilirubin, cholesterol, total protein, calcium, magnesium, phosphorus). It demonstrated the need for the use of routine appropriate internal quality control in all laboratories. The proficiency test programme should be extended to all clinical laboratories and target all biology disciplines.